Kehujahan Hadist Nabi Dalam Ajaran Islam - N, Nurfadillah; R, Rezkisitihajar; Bacomiro, Abbas (Madani: Jurnal Ilmiah Multidisiplin, 2025)
In the science of hadith and ushul fiqh, hadith is classified based on its level of quality. Fatkhul Wahab (2019) states that authentic and hasan hadith constitute Shari’a proof because they meet the requirements of continuous sanad, fair guardianship and dhabit, as well as being free from defects (‘illat) and deviations (syadz). This is reinforced by Lestari & Fahmi who assert that authentic hadith forms a strong basis of proof in Islamic law because it is viewed as having strict scientific validity in accordance with the methodology of hadith science. The majority of Muslim scholars since the generation of the Companions agree that the hadith of the Prophet is proof in establishing the law. In Al-Mustashfa, al-Ghazali mentions that ijma’ on the obscenity of hadith is a firm foundation in legal instinbat (al-Ghazali, al-Mustashfa fi Ilm al-Usul, 1993). The majority of Ahl al-Sunnah wal Jama’ah scholars agree that the hadith—especially the shahih ones—constitute a legally binding and authoritative source of argument. The views of the imams on the authenticity of the hadith also strengthened their position in Islamic science. M. Nasri Hamang states that the four major schools (Hanafi, Maliki, Shafi’i, and Hanbali) accept hadith as Shari’a proof, although there are differences in approach in assessing types of hadith such as ahad, mutawatir, and mursal. In the view of Imam Shafi’i, as explained by Moh. Ahfas, hadith has the same position as the Qur’an in establishing the law, and every hadith that is sahih of the Prophet is obligatory to accept and practice.